Theory Of Relativity For GPS And Its Application In Determining The Geographical Location Of Students' Address - Ahmad Amin; Armi Yuneti; Aceng Ruyani (Postgraduate, University of Mataram, 2025)
This study aims to determine the working principle of the Global Positioning System (GPS) as a technology that applies the concept of relativity, and its application to determine the geographic location of students' addresses. This type of research is a literature study. In general, the GPS system has three main components, namely the ground segment (control station), the space segment (satellite), and the user segment (receiver device). GPS determines the receiver's position using the trilateration method from a minimum of four satellites that are always visible from any point on Earth at any time. The results of the study state that information from three satellites is needed to determine location, while the fourth signal is needed to determine time accurately. Relativity causes the GPS system to experience a time lag. The relative motion of the satellite to the earth causes the time on the satellite to be slower than earth time, while earth's gravity makes the satellite time move faster than earth time. The novelty of the results and discussion of the study conducted is to find the coordinates of student addresses, thus facilitating mapping of student residences in the city of Lubuklingau and its surroundings.